The Effect of Transformational Leadership and Job Autonomy on Employee Performance: The Mediating Role of Innovative Work Behavior - Sasmitha, Jonathan Lucky Sasmitha; Sobandi, A; Suryadi, E; Rofaida, Rofi (Ilomata International Journal of Management, 2024)
This research explores the effect of transformational leadership and work autonomy on employee performance through the role of innovative work behavior as a mediator. This study uses a quantitative approach with data collection through a survey involving 45 marketers from various industries as respondents in this study. The questionnaire results were then analyzed using PLS-SEM software. The findings show that transformational leadership positively and significantly influences employee performance and this influence can be explained through the mediating effect of innovative work behavior. However, the opposite result was found between work autonomy and employee performance where work autonomy did not positively and significantly influence employee performance. Managers can enhance marketing personnel performance by implementing transformational leadership. This leadership style fosters innovative work behavior which is very useful for overcoming problems and challenges at work.